Issues & Observations : Reflections on Leadership in Troubled Waters - Chappelow, Craig (Center for Creative Leadership, 2001)
How do you deal with a crisis? Do you panic and flounder, or do you keep a clear head and figure out exactly what is needed to solve the problem? This article recounts an experience that author had while boating and what it taught him about crisis leadership.